2014
DOI: 10.1097/mib.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Combination Therapy with Immune Modulators on Anti-TNF Trough Levels and Antibodies in Patients with IBD

Abstract: The influence of combination therapy with IM on TL and antibodies to anti-tumor necrosis factor medication was significant for IFX-treated patients. Patients who started combination therapy immediately developed antibodies less often than patients who started later with concomitant medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 18 publications
0
31
1
4
Order By: Relevance
“…83 84 Retrospective studies of adalimumab combination therapy are also inconclusive. 85 86 Immunogenicity data were not collected in the CHARM maintenance trial for adalimumab, but data from the pivotal certolizumab maintenance trial showed similar rates of antibody formation to infliximab when stratified for dosing schedules and immunomodulator use, suggesting that there should be a role for concomitant immune suppression with an injectable anti-TNF agent. 72 87 Ideally, early therapeutic drug monitoring (TDM) could be used to prevent loss of response rather than to reverse loss of response.…”
Section: Postoperative Anti-tnf Prophylaxismentioning
confidence: 99%
“…83 84 Retrospective studies of adalimumab combination therapy are also inconclusive. 85 86 Immunogenicity data were not collected in the CHARM maintenance trial for adalimumab, but data from the pivotal certolizumab maintenance trial showed similar rates of antibody formation to infliximab when stratified for dosing schedules and immunomodulator use, suggesting that there should be a role for concomitant immune suppression with an injectable anti-TNF agent. 72 87 Ideally, early therapeutic drug monitoring (TDM) could be used to prevent loss of response rather than to reverse loss of response.…”
Section: Postoperative Anti-tnf Prophylaxismentioning
confidence: 99%
“…Higher IFX trough concentrations have been found in IBD patients receiving both IFX and concomitant immunomodulator treatment compared with the IFX monotherapy group (7.5 vs. 4.6 lg/ml, p = 0.04) [194]. The addition of an immunomodulator to IBD patients receiving anti-TNF monotherapy, with loss of response due to immunogenicity, has been shown to result in undetectable ADAs, increased serum drug concentrations and regained clinical response [193].…”
Section: Pharmacokinetic and Pharmacodynamic Considerationsmentioning
confidence: 99%
“…The use of immunomodulatory agents, specifically thiopurines (6-mercaptopurine and azathioprine) and methotrexate has been shown to increase circulating antitumor necrosis factor levels and decrease the formation of antitumor necrosis factor neutralizing antibodies, particularly in the case of infliximab [1,2]. The efficacy of using the combination of infliximab with azathioprine was definitively proven in the landmark SONIC trial [3], which showed that this strategy was superior to both azathioprine or infliximab monotherapy in both inducing and maintaining deep remission and in promoting mucosal healing [4 & ].…”
Section: Introductionmentioning
confidence: 99%